Characterization of fillets of Amazon and real hybrid sorubins - Cavenaghi-Altemio, Angela Dulce; Macedo, Adriane; Piccoli, Andressa; Graciano Fonseca, Gustavo (Vitae, 2023)
Background: There are few studies on the evaluation of meat from hybrid sorubins. Objective: Thus, the aim of this work was to evaluate the physical, chemical, microbiological and sensorial characteristics of fillets of Amazon and real hybrid sorubins. Method: Proximate composition, instrumental colour, water holding capacity, cooking losses and shear force were measured. Microbiological analyses of the fillets were carried out for Salmonella sp. and Staphylococcus aureus to ensure food safety of the judges during sensory analysis. Results: Hybrid sorubim fillets presented an excellent quality, being classified in category A (lipids below 5% and proteins between 15% and 20%). There was no significant difference (p>0.05) between the evaluated fillets for several parameter: the average water holding capacities were 33.72 and 34.67%, the cooking losses were 14.93 and 13.41%, the shear forces were 2.21 and 1.74 kgf, and the luminosities were 49.61 and 45.04 for the fillets of Amazonian hybrid sorubim and real hybrid sorubim, respectively. Discussion: There was an evident relation between water holding capacities and shear forces. Amazonian hybrid sorubim fillets were more accepted due to their lower intensity of red. However, there was no sensorial difference between the hybrids, and both had an acceptance rate above 80%. Conclusion: It was concluded that the hybridization does not alter the sensory characteristics of the fish fillets.